Simulation Research on Dynamic Characteristics of Hydraulic Mount - Yanhua Liu; Xin Guan; Pingping Lu; Rui Guo (Chinese Journal of Mechanical Engineering, 2021)
Abstract At present, research on hydraulic mounts has mainly focused on the prediction of the dynamic stiffness and loss angle. Compared to the traditional finite element analysis method, the programming method can be used to analyze hydraulic mounts for a rapid and accurate understanding of the influence of the different mounting parameters on the dynamic stiffness and loss angle. The aims of this study were to investigate the nonlinear dynamic characteristics of a hydraulic mount, and to identify the parameters that affect the dynamic stiffness and loss angle using MATLAB software programs to obtain the influence curves of the parameters, so as to use suitable parameters as the basis for vibration analysis. A nonlinear mechanical model of a hydraulic mount was established according to the basic principles of fluid dynamics. The dynamic stiffness and loss angle of the dimensionless expression were proposed. A numerical calculation method for the dynamic performance evaluation index of the hydraulic mount was derived. A one-to-one correspondence was established between the structural parameters and peak frequency of the evaluation index. The accuracy and applicability of the mechanical model were verified by the test results. The results demonstrated the accuracy of the nonlinear mechanical model of the hydraulic mount, and the vehicle driving comfort was greatly improved by the optimization of the structural parameters.